2004
DOI: 10.1002/ps.792
|View full text |Cite
|
Sign up to set email alerts
|

Biology and integrated control of Pestalotiopsis on container‐grown ericaceous crops

Abstract: Pestalotiopsis isolates obtained from the foliage, stem-base and roots of diseased container-grown ericaceous crops (Calluna, Erica, Pieris and Rhododendron) collected from UK nurseries were identified as Pestalotiopsis sydowiana (Bresad) B Sutton on the basis of conidia morphology. Inoculum sources of the pathogen included diseased stock plants, crop debris, nursery soils, used growing media, pots and floor covering, and dust collected from greenhouse walkways. Isolates were not host-specific and infected oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
(14 reference statements)
1
17
0
Order By: Relevance
“…Secondary inoculum produced on diseased tissue may cause secondary infections and increase the severity of the disease. The source of the inoculum can be wild plantations (Keith et al 2006), flowers (Pandey 1990), crop debris, disease stock plants, used growing media, soil and contaminated nursery tools (McQuilken and Hopkins 2004), splashed water droplets (Hopkins and McQuilken 1997;Elliott et al 2004) and also spores in the air (Xu et al 1999). Species of Pestalotiopsis have constantly been isolated as endophytes from plant tissues (Wei and Xu 2004;Liu et al 2006;Wei et al 2005Wei et al , 2007Tejesvi et al 2009;Watanabe et al 2010).…”
Section: Life Cycle In Pestalotiopsismentioning
confidence: 97%
“…Secondary inoculum produced on diseased tissue may cause secondary infections and increase the severity of the disease. The source of the inoculum can be wild plantations (Keith et al 2006), flowers (Pandey 1990), crop debris, disease stock plants, used growing media, soil and contaminated nursery tools (McQuilken and Hopkins 2004), splashed water droplets (Hopkins and McQuilken 1997;Elliott et al 2004) and also spores in the air (Xu et al 1999). Species of Pestalotiopsis have constantly been isolated as endophytes from plant tissues (Wei and Xu 2004;Liu et al 2006;Wei et al 2005Wei et al , 2007Tejesvi et al 2009;Watanabe et al 2010).…”
Section: Life Cycle In Pestalotiopsismentioning
confidence: 97%
“…At the time of its implementation, MRLs will exist for about 750 chemicals. Pesticides are applied to agricultural crops throughout the entire world to control undesirable insects, 1,2) mites, 3,4) fungi, 5,6) weeds, 7,8) nematodes 9,10) and mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that successful Pestalotiopsis infection cannot be established without first artificially wounding its host (Espinosa and Briceno 2008;McQuilken and Hopkins 2004). Since vegetative propagation involves cutting of vegetative propagules, and therefore results in wounding, a fungicide treatment scheme should be integrated into the mass propagation cutting system.…”
Section: Phytoprotection 90 : 117-120mentioning
confidence: 99%
“…They have been reported to be saprobes, endophytes and facultative pathogens (Hu et al 2007;Metz et al 2000), are ubiquitous in distribution and are found on a wide range of substrates (Jeewon et al 2003;Thaung 2008). Also, they are not host-specific (Hu et al 2007) and can thrive over a wide range of temperatures, pH and matric potentials (Hopkins and McQuilken 2000;McQuilken and Hopkins 2004), indicating that they are adapted to a range of environmental conditions. Pestalotiopsis clavispora is associated with many plant species growing in various parts of the world (Morgan et al 1998; USDA 2009), including South Africa, Australia, the USA and Egypt, where Argania spinosa has already been introduced.…”
Section: Phytoprotection 90 : 117-120mentioning
confidence: 99%